An update on tropical Ctenidae from Jamaica (Arachnida: Araneae) - Polotow, Daniele; Brescovit, Antonio D. (Zootaxa, 2012)
The two known species of Ctenidae from Jamaica are redescribed: Acanthoctenus remotus Chickering, 1960 and Ctenusmalvernensis Petrunkevitch, 1910. One new species is described, Ctenus catherine sp. nov., based on a single male. All three species are known only from Jamaica.